2014
DOI: 10.3741/jkwra.2014.47.9.789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inland Inundation Risk in Urban Area using Fuzzy AHP

Abstract: This study presented how to evaluate the inland inundation risk considering the characteristics of inland flood. Fuzzy AHP (Analytic Hierarchy Process), which can deal with the uncertainty or ambiguousness of the decision-making process, was used to estimate the inundation risk. The criteria used for inland inundation risk include the physical index, social index and inland flood. Each index contains three detailed indicators then total nine indicators were employed in this study. The inundation risk evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…그러나 인류의 발전은 양날 의 검과도 같이 지구온난화, 기후변화, 생태계 파괴 등과 같은 다양한 형태로 우리에게 위협을 가해왔다 (Yu, 2017 (Kim et al, 2012;Park, 2012;Song, 2012;KEI, 2014 ;Park et al, 2014;Cho, 2015;Han et al, 2015;Hwang, 2015;Nam, 2015 (Son et al, 2013). 이와 같이 위험도뿐 만 아니라 기후변화의 취약성 평가에 대한 연구는 최근 들어 국내외적으로 활발하게 진행되고 있다 (IPCC, 2001;Kelly and Adger, 2000;Moss et al, 2001;Brooks et al, 2005;Eriksen and Kelly, 2007 (Lee and Chang, 2014;Shin et al, 2014;Choi et al, 2015;Oh et al, 2015;Jeong et al, 2016;Park et al, 2016;Shin, 2016 Fig. 1(a)], 설계빈도에서의 침수심[ Fig.…”
Section: 서 론unclassified
“…그러나 인류의 발전은 양날 의 검과도 같이 지구온난화, 기후변화, 생태계 파괴 등과 같은 다양한 형태로 우리에게 위협을 가해왔다 (Yu, 2017 (Kim et al, 2012;Park, 2012;Song, 2012;KEI, 2014 ;Park et al, 2014;Cho, 2015;Han et al, 2015;Hwang, 2015;Nam, 2015 (Son et al, 2013). 이와 같이 위험도뿐 만 아니라 기후변화의 취약성 평가에 대한 연구는 최근 들어 국내외적으로 활발하게 진행되고 있다 (IPCC, 2001;Kelly and Adger, 2000;Moss et al, 2001;Brooks et al, 2005;Eriksen and Kelly, 2007 (Lee and Chang, 2014;Shin et al, 2014;Choi et al, 2015;Oh et al, 2015;Jeong et al, 2016;Park et al, 2016;Shin, 2016 Fig. 1(a)], 설계빈도에서의 침수심[ Fig.…”
Section: 서 론unclassified
“…They conducted studies to apply context-specific, precise and reliable tools to enlist the essential variables and estimate the harmful impacts of climate change on different dimensions (availability, accessibility, utilization and sustainability) of food security [9][10][11][12][13]. After a preliminary literature review, we found that previous studies in different countries addressed the acceptable validity of the AHP method to identify the important indicators with accurate weights and use these indicators to predict the uncertainties in various subjects, e.g., environment or food and agriculture [14][15][16][17][18][19][20]. Moreover, lessons learned from other countries which tried to improve their adaptation policies evidenced that the development of tools to measure leading climate change and food security indices by the AHP questionnaire is helpful [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…al [25] used FAHP in the selection of robotic system in a manufacturing plant. FAHP is used in a supplier selection in a washing machine company [26], evaluation of inland inundation risk in urban area [27], unban land-use planning [28], and robot path selection problem [29].…”
Section: Introductionmentioning
confidence: 99%